Real Time Monitoring for the Most Vulnerable: UNICEF's Experience in Uganda. (21st March 2013) - Cummins, Matthew; Huddleston, Barbara
Abstract This article reviews two Real Time Monitoring (RTM) initiatives in Uganda that utilise RapidSMS technology. mTrac uses mobile phones to transmit local health information, including disease surveillance, malaria treatment and drug stocks. This electronic‐based reporting system replaced a paper‐based one, enabling actionable information to be delivered more quickly. Its early success in Uganda suggests that similar systems could be introduced elsewhere to achieve cost‐savings and more efficient monitoring of key supply and demand health indicators in vulnerable areas. U‐report offers young Ugandans a chance to voice their opinions on pertinent issues by giving them access to a free SMS service through which they can send in text messages, respond to polls, and receive factual information and results. Although the objective is to empower all youth, U‐reporters often tackle issues that address the needs of vulnerable children and communities. The ability to target polls by regions is an exciting feature, and further research is warranted to better understand U‐report's sampling potential.